2020
DOI: 10.1002/trc2.12021
|View full text |Cite
|
Sign up to set email alerts
|

Brain tocopherol levels are associated with lower activated microglia density in elderly human cortex

Abstract: Introduction Higher brain tocopherol levels have been associated with lower levels of Alzheimer's disease (AD) neuropathology; however, the underlying mechanisms are unclear. Methods We studied the relations of α‐ and γ‐tocopherol brain levels to microglia density in 113 deceased participants from the Memory and Aging Project. We used linear regression analyses to examine associations between tocopherol levels and microglia densities in a basic model adjusted for age, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A metaanalysis of 31 articles indicated that individuals with AD, age-related cognitive impairment, or mild cognitive decline had lower circulatory concentrations of α-tocopherol compared to healthy controls [126]. Additionally, an analysis of 115 deceased and autopsied cases in the Rush Memory and Aging Project showed that higher levels of brain tocopherols such as α-tocopherol were related to lower activated microglia density in the cortical brain, which might protect against AD to lower levels of inflammation, amyloid, and neurofibrillary tangle severity [127].…”
Section: Almonds and Metabolic Health Biomarkers And Outcomesmentioning
confidence: 99%
“…A metaanalysis of 31 articles indicated that individuals with AD, age-related cognitive impairment, or mild cognitive decline had lower circulatory concentrations of α-tocopherol compared to healthy controls [126]. Additionally, an analysis of 115 deceased and autopsied cases in the Rush Memory and Aging Project showed that higher levels of brain tocopherols such as α-tocopherol were related to lower activated microglia density in the cortical brain, which might protect against AD to lower levels of inflammation, amyloid, and neurofibrillary tangle severity [127].…”
Section: Almonds and Metabolic Health Biomarkers And Outcomesmentioning
confidence: 99%
“…We acknowledge that this exploratory study is limited by a relatively small sample size (which is reflected by borderline significant p-values in Supplementary Table 4B) of mostly Caucasian women, and the inability to control for other covariates that may affect cognitive function such as alcohol and smoking history, physical activity, social interactions, and genetics (83). However, nutrient profiles and concentrations in this current analysis are similar to those of other cohorts of older adults (29)(30)(31)(84)(85)(86)(87)(88). NP1, described mostly by high fat content, was not associated with cognition in this population.…”
Section: Discussionmentioning
confidence: 81%
“…Given that high Aβ level sustained over a long period of time may increase Aβ catabolism, unaltered Aβ synthesis as observed by Arrozi et al could be explained by the treatment period of over six months [ 101 ]. A study investigating TP levels in the human cortex observed an association between higher α- and γ-TP levels and lower total and activated microglia density in cortical regions, suggesting a microglia-mediated beneficial effect on the slowly accumulating AD neuropathology [ 21 ]. In later stages of AD, continued microglial activation can exacerbate tau pathology and negatively affect neurons and synapses [ 103 , 104 ].…”
Section: Vitamin E Can Fuel the Pathogenesis Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…In contrast, patients with low cholesterol, minimal inflammatory burden and little oxidative stress may be adversely affected by supplementation. Regarding the effects of α- and γ-TP on activated microglial cell density [ 21 ], supplementation can lead to either desirable or detrimental effects, dependent on disease progression and method of administration.…”
Section: Is Vitamin E Supplementation Suitable For Everyone?mentioning
confidence: 99%